Implementasi Metode Diskusi pada Pembelajaran Pendidikan Agama Islam - Nurhayati Nurhayati; Sulaiman Sulaiman (Prodi Pendidikan Keagamaan Islam, 2022)
The background of this research is the low interest of students in learning because the learning method is not of interest to students. This study aims to find out (1) how the implementation of the discussion method in PAI learning for class XI MIPA students at SMA 2 Sijunjung, what are the weaknesses and strengths of the discussion method, (3) what are the supporting factors and inhibiting factors of the discussion method. This type of research is qualitative research with a descriptive method. This research was conducted at SMAN 2 Sijunjung. The informants of this study were the principal, curriculum representative, PAI teacher, 3 students of class XI MIPA. Data collection techniques in this study were by observing, interviewing, and recording the ongoing interviews. The results of this study are about implementing the discussion method in learning through the classroom system so that students are excited and happy to follow the process.